2013
DOI: 10.1155/2013/202497
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Clinically Relevant Safety Signals of Nephrotoxicity through Plasma Metabolite Profiling

Abstract: Addressing safety concerns such as drug-induced kidney injury (DIKI) early in the drug pharmaceutical development process ensures both patient safety and efficient clinical development. We describe a unique adjunct to standard safety assessment wherein the metabolite profile of treated animals is compared with the MetaMap Tox metabolomics database in order to predict the potential for a wide variety of adverse events, including DIKI. To examine this approach, a study of five compounds (phenytoin, cyclosporin A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…Our study revealed changes in metabolites of purines, glutathione and amino acids upon exposure to tubular neurotoxicants. Similar alterations were also described in plasma and kidney tissue of rats exposed to different drugs associated with tubular damage ( Boudonck et al, 2009 ; Zgoda-Pols et al, 2011 ; Mattes et al, 2013 ). Those metabolic changes can be linked with alterations in energy metabolism, xenobiotic metabolism and protein catabolism, which have already been described in the pathophysiology of acute kidney injury ( Druml, 2013 ).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our study revealed changes in metabolites of purines, glutathione and amino acids upon exposure to tubular neurotoxicants. Similar alterations were also described in plasma and kidney tissue of rats exposed to different drugs associated with tubular damage ( Boudonck et al, 2009 ; Zgoda-Pols et al, 2011 ; Mattes et al, 2013 ). Those metabolic changes can be linked with alterations in energy metabolism, xenobiotic metabolism and protein catabolism, which have already been described in the pathophysiology of acute kidney injury ( Druml, 2013 ).…”
Section: Discussionsupporting
confidence: 72%
“…The COMET and MetaMap ® To x projects are two examples of the potential of toxicometabolomics as a drug toxicity screening tool. Those studies generated metabolic databases from urine and plasma samples of rats exposed to different toxicants that were further used to predict specific organ toxicity, including DIRI ( Ebbels et al, 2007 ; van Ravenzwaay et al, 2012 ; Mattes et al, 2013 ). Toxicometabolomics proved also to be useful to identify new biomarkers and/or elucidate the mechanisms underlying DIRI.…”
Section: Introductionmentioning
confidence: 99%
“…A biomarker panel based on pathways or common mechanisms of hepatotoxicity would be ideal for the prediction of liver injury [40] . The metabolic profiling has been successfully used to predict drug induced kidney injury in a preclinical study [41] . Hence, our efforts to discover a metabolic biomarker panel for prediction of liver injury will be based on the common pathways underlying hepatotoxicity: i) bile acid metabolism; ii) oxidative stress, iii) energy pathways related to mitochondrial impairment and iv) other hepatic cell regeneration pathways [40] .…”
Section: Resultsmentioning
confidence: 99%
“…2500 metabolites, 1200 drugs and 3500 food components encountered in the human body (Wishart et al, 2007), the MetaMap®-Tox developed at metabonomics and containing rat plasma metabolome for more than 500 references compounds Mattes et al, 2013). 2500 metabolites, 1200 drugs and 3500 food components encountered in the human body (Wishart et al, 2007), the MetaMap®-Tox developed at metabonomics and containing rat plasma metabolome for more than 500 references compounds Mattes et al, 2013).…”
Section: Principles Of Metabolomicsmentioning
confidence: 99%